A Systematic Review: The Implementation of MALL toward Students’ Reading Skill - Fortuna Dewi, Wanda Dian Paramesti; Made Hery Santosa (Universitas Pendidikan Ganesha, 2022)
Mastering English language has become primary need around the world nowadays. Unfortunately, students still face many challenges in learning English and one of them reading skill. The development of technology brings many advantages towards English language learning. Many researchers have conducted studies about the effect of technology in the learning process, however, still few reviewed studies on the effect of MALL in reading skill among EFL and ESL learners at secondary level. Therefore, this study aims to analyses the effect of implementing MALL toward students’ reading skill among EFL and ESL learners. This study use PRISMA model to select the article based on the inclusion criteria. The study conducted using systematic method by synthesize relevant information from previous studies. 13 articles were chosen from 49 articles that represent the topic taken from Google Scholar as the main data resources. The studies revealed that MALL has positively affect students’ reading skill. MALL increases students’ reading comprehension, motivation, participation and interaction in reading lesson.